Let's evaluate each statement:
1. g(x) = f(x + 3)
- Substituting the expressions for f(x) and g(x), we get:
6x + 15 = 2(x + 3) + 5
6x + 15 = 2x + 6 + 5
6x + 15 = 2x + 11 (Incorrect)
2. g(x) = f(3x)
- Substituting the expressions for f(x) and g(x), we get:
6x + 15 = 2(3x) + 5
6x + 15 = 6x + 5 (Incorrect)
3. g(x) = f(x) + 3
- Substituting the expressions for f(x) and g(x), we get:
6x + 15 = 2x + 5 + 3
6x + 15 = 2x + 8 (Incorrect)
4. g(x) = 3 . f(x)
- Substituting the expressions for f(x) and g(x), we get:
6x + 15 = 3(2x + 5)
6x + 15 = 6x + 15 ) (Correct)
So, the correct statement is g(x) = 3 . f(x).